PELAKU BULLYING DAN NILAI KARAKTER PESERTA DIDIK DI SMK LABOR BINAAN FKIP UNRI - Monica Octaryenza; Rosmawati Rosmawati; Zulfaan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Bullying is an individual action to bully others repeatly, physically and verbally. It is important to apply the characters education at school. By applying this, students can instil the education value, moral education, and good characters education so they can avoid bullying from others. The purpose of this research was to know the description of the bullies and their values character at school. A student who called the bullies if he/she bully his/her friends verbally or physically. The subject of this research were 24 bullies students, by using purposive sampling. This research used descriptive method with quantitative approach, a closed questionnaire as its instrument and the percentage formula to analyze the data. The results of the study have shown that the bullies behavior were in the medium category while their character values were in good category. The conclusion were the male students were more often bullying his friends than female students, they bully their friends physically. The character values of these bullies were in good category, which seen from their responsibility, tolerance, emphaty, well-mannered and their self control.Keywords: Character Values, Bullies